Evolutionary shifts in taste coding in the fruit pest Drosophila suzukii - Dweck, Hany KM (eLife, 2021)
Although most Drosophila species lay eggs in overripe fruit, the agricultural pest Drosophila suzukii lays eggs in ripe fruit. We found that changes in bitter taste perception have accompanied this adaptation. We show that bitter-sensing mutants of Drosophila melanogaster undergo a shift in egg laying preference toward ripe fruit. D. suzukii has lost 20% of the bitter-sensing sensilla from the labellum, the major taste organ of the head. Physiological responses to various bitter compounds are lost. Responses to strawberry purées are lost from two classes of taste sensilla. Egg laying is not deterred by bitter compounds that deter other species. Profiling of labellar transcriptomes reveals reduced expression of several bitter Gr genes (gustatory receptors). These findings support a model in which bitter compounds in early ripening stages deter egg laying in most Drosophila species, but a loss of bitter response contributes to the adaptation of D. suzukii to ripe fruit.